Incidence and Short- to Intermediate-Term Oncological Outcomes of Pathological T0 Prostate Cancer After Robot-Assisted Radical Prostatectomy: A Multicenter, Retrospective Cohort Study in Japan (MSUG94 Group). - Tomioka-Inagawa, Risa; Tomioka, Masayuki; Tatenuma, Tomoyuki; Sasaki, Takeshi; Ikehata, Yoshinori; Nakayama, Akinori; Toide, Masahiro; Yoneda, Tatsuaki; Sakaguchi, Kazushige; Makiyama, Kazuhide; Inoue, Takahiro; Kitamura, Hiroshi; et al. (Current Oncology, 2026)
Simple Summary: Pathological T0 prostate cancer indicated that no residual tumor was found in the prostatectomy specimen despite a positive biopsy. This phenomenon remains poorly understood, particularly regarding whether the absence of cancer truly indicates a favorable outcome. We analyzed 3079 Japanese men who underwent robot-assisted prostate removal at nine medical centers. Only 27 patients (0.9%) had pathological T0 disease, 23 of whom had received neoadjuvant hormonal therapy (NHT). Four patients had pathological T0 disease without NHT, and none developed biochemical recurrence during the limited follow-up period. In the NHT subgroup, pathological T0 was associated with numerically favorable 2-year biochemical recurrence-free survival, although the analysis was exploratory because only two events occurred in the pathological T0 group. These findings indicate that pathological T0 after radical prostatectomy is rare in Japan and should be interpreted with caution, especially when it follows NHT. Given the possibility that late-onset recurrences may have been overlooked, the results of this trial should be understood as providing evidence from the short- to intermediate-term perspective. Background: Pathological T0 (pT0) prostate cancer following radical prostatectomy is uncommon, and its prognostic significance remains unclear, particularly after neoadjuvant hormonal therapy (NHT). We investigated the incidence of pT0 disease in a multicenter Japanese cohort and described postoperative biochemical recurrence (BCR) outcomes. Methods: This retrospective study analyzed 3079 patients who underwent robot-assisted radical prostatectomy at nine Japanese centers between 2011 and 2021. Patients were classified as having pT0 or non-pT0 disease. Because only four pT0 cases occurred without NHT, these are summarized descriptively. Exploratory Kaplan–Meier and log-rank analyses of biochemical recurrence-free survival (BRFS) were performed for the NHT subgroup. Results: Twenty-seven pT0 cases (0.9%) were identified, and 85.2% were identified after NHT. Overall, 399 patients (13.0%) developed BCR. Among patients who did not undergo NHT, the 1- and 2-year BRFS rates were 100% and 100%, respectively, in the pT0 group and 92.4% and 88.1%, respectively, in the non-pT0 group. In the NHT subgroup, the corresponding rates were 92.9% and 92.7%, versus 91.8% and 85.5%, respectively (p = 0.651). Conclusions: pT0 disease after robot-assisted radical prostatectomy is rare and occurs predominantly after NHT. Given the possibility that late-onset recurrences may have been overlooked, the results of this trial should be understood as providing evidence from the short- to intermediate-term perspective.